2006
DOI: 10.1002/chp.69
|View full text |Cite
|
Sign up to set email alerts
|

The difficulty with experience: Does practice increase susceptibility to premature closure?

Abstract: Physicians with greater experience appear to weigh their first impressions more heavily than those with less experience. Educators should design instructional activities that account for experience-specific cognitive tendencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
56
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 17 publications
1
56
1
Order By: Relevance
“…For example, Eva and colleagues showed that experienced physicians were prone to the primacy effect, a cognitive bias describing the tendency to choose an incorrect diagnosis when its features are presented earlier in the case, 26 in comparison with features of the correct diagnosis that are presented later. 28 This suggests the intriguing possibility that the primary beneficiaries of CFS may be experts and not novices, in contrast to the arguments suggested in diagnostic reasoning editorials. Future research should explore this hypothesis.…”
Section: Discussionmentioning
confidence: 96%
“…For example, Eva and colleagues showed that experienced physicians were prone to the primacy effect, a cognitive bias describing the tendency to choose an incorrect diagnosis when its features are presented earlier in the case, 26 in comparison with features of the correct diagnosis that are presented later. 28 This suggests the intriguing possibility that the primary beneficiaries of CFS may be experts and not novices, in contrast to the arguments suggested in diagnostic reasoning editorials. Future research should explore this hypothesis.…”
Section: Discussionmentioning
confidence: 96%
“…Overestimating the posterior probability after a negative test can also lead to refusing to stop testing a patient, potentially leading to false positives and side-effects from testing. In fact, premature closure and misjudging the usefulness of a finding are two of the most common cognitive errors believed to cause diagnostic mistakes (Croskerry, 2002;Croskerry, Singhal, & Mamede, 2013;Eva & Cunnington, 2006;Graber, Franklin, & Gordon, 2005;Graber et al, 2012;Reilly, Ogdie, Von Feldt, & Myers, 2013;Voytovich, Rippey, & Suffredini, 1985). Consequently, it is important to understand more broadly how well physicians and other experts perform Bayesian reasoning in more realistic situations with their own beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…However, while System 1 reasoning is a hallmark of the experienced physician, errors may result from an overreliance on automatic reasoning. 40 Most clinical scenarios require both systems. This combined approach, often referred to as "dual processing," likely offers the best chance at diagnostic success, even for novices.…”
Section: Introductionmentioning
confidence: 99%